Self-in-Relation: Seeking Understanding and Transformation through Indigenous Métissage - Dr. Heather Bensler (Journal of Applied Hermeneutics, 2025)
In this article, I consider the narrative practice of Indigenous Métissage as a creative, subversive praxis to help understand my identity as a settler in Canada and how settler colonialism has shaped my relationship to Indigenous peoples, history, and Land in Canada. Given the hermeneutic roots of Indigenous Métissage, I suggest it is a research approach that can handle the complexities inherent in these relationships while also providing imagination and hope for transformation. I discuss how personal, and family stories can be textually braided with larger national narratives to draw attention to similarities and differences with the hopes of provoking understanding and new ways of seeing Indigenous and settler relations.